HUBUNGAN ANTARA TINGKAT PEKERJAAN DENGAN USIA KEJADIAN MENOPAUSE DI DESA BUMIREJO KECAMATAN KEBUMEN - Hastin Ika Indriyastuti; Adinda Putri Sari Dewi; Miftah Shifa (Jurnal Ilmiah Kesehatan Keperawatan, 2015)
Menopause is one of phases experienced by women. It is a biological condition when women do not experience menstruation anymore. The age of menopause is different between one woman to another. There are some factors influencing menopause such as the first time when experiencing the menstruation (menarche), physiological and job condition, the number of children, the contraception usage, smoking, social economic condition, weather, and the height of geographic condition. The objective of the research is finding out correlation between Job level with age of menopause occurrence in Bumirejo Village KebumenThis study is  to find out correlation between Job level with age of menopause occurrence in Bumirejo Village Kebumen.This is an analytic correlation research using cross sectional approach. The population consisted of 511 of 45-55 years old women in Bumirejo in 2014. The samples are 128 respondents taken by purporsive sampling technique.  The research instrument is questioner. The data analysis technique is Chi Square test with significant level 0.05.This study shod that there are 72 respondents (56.3%) had heavy job and 56 respondents (43.8%) had easy job. Respondents who experienced normal menopause = 95 respondents (74.2%), earlier menopause = 21 respondents (16.4%) and slow menopause = 12 respondents (9.4%). There is a significant correlation between Job level with age of menopause occurrence with X2 count > X2 table (14.693 > 5.991). Keywords     : job level, menopause